Suomen väyläadpositioiden prepositio- ja postpositiokäyttöjen merkityseroista [On meaning differences between prepositional and postpositional uses of Finnish path adpositions] - Huumo, Tuomas (Virittäjä, 2010)
(Itämeren)suomen adpositiojärjestelmän erikoisuuksia on, että etenkin väylää tai suuntaa ilmaisevia adpositioita voidaan usein käyttää sekä prepositioina että postpositioina: Juoksin pitkin siltaa ~ siltaa pitkin; Hän käveli läpi metsän ~ metsän läpi; Kirkko on keskellä kylää ~ kylän keskellä (systeemistä ja sen historiasta ks. Grünthal 2003, 2005) Prepositio- ja postpositioversioiden eroja on kirjallisuudessa luonnehdittu lähinnä stilistisiksi (mm. ISK 2004: 690), mutta niitä erottaa toisinaan myös merkitys: esimerkiksi aikaa ilmaistaan luontevammin prepositiolla (Surffailin netissä pitkin päivää ~ ?päivää pitkin; Maassa tapahtui vallankaappauksia läpi 1970-luvun ~ ?1970-luvun läpi). Myös spatiaalisissa käytöissä on havaittu merkityseroja preposition ja postposition välillä – Leino (1993: 218) toteaa, että ilmaukset kautta Suomen, pitkin maata ja ympäri kylän ~ kylää eivät tarkoita samaa kuin Suomen kautta, maata pitkin ja kylän ympäri, sillä prepositiot ilmaisevat imperfektiivistä väylää, postpositiot kolmiulotteista tilaa. Keskellä- ja ympäri-adpositioista samantapaisia merkityseroja havaitsee Haukioja (1998) ja yli-adpositiosta Salmi (1994: 170–172), joka toteaa, että prepositiona yli pystyy ilmaisemaan mm. tarkoitteen hajanaista esiintymistä kiintopistealueella (Haapaa kasvaa yli koko Suomen, Kesällä muikkuparvet ovat hajaantuneina yli järvien). Tämäntapaiset hajanaista sijaintia tai levittäytymistä kuvaavat lauseet kytkeytyvät fiktiivisen liikkeen nimellä tunnettuun ilmiöön (Talmy 2000: luku 2), sillä niissä käsitteistäjän näkökulma ei seuraa osallistujan liikettä vaan liukuu staattisen tilanteen yli havainnoiden, mitä kiintopistealueella esiintyy. Artikkelissa tarkastellaan väyläadpositioiden prepositiokäyttöjä ja niiden erikoistehtäviä kontrastoiden niitä postpositiokäyttöihin. Päähavaintona on, että postpositio edustaa luontevimmin väylän liikkeeseen pohjaavaa käsitteistystä, jossa väylä esitetään perfektiivisenä ja konstruoidaan holistisesti etänäkökulmasta. Prepositio taas pystyy ilmaisemaan myös puhtaasti subjektiivista, "skannaukseen" pohjaavaa suuntaista käsitteistystä, jossa väylä esitetään imperfektiivisenä ja konstruoidaan lokaalisesti lähinäkökulmasta. Tarkastelun tukena ja vertailukohtana ovat suomen kielen terminatiivisia ilmauksia koskevat Alhoniemen (1978) sekä Päiviön (2007) tutkimukset. Väyläadpositioiden tapaan terminatiivi-ilmaukset (jostain asti / johonkin saakka) kuvaavat väyliä, joilla liikutaan tai joiden varrella esiintyy jotakin. Alhoniemen (1978) esittämä terminatiivi-ilmausten luokittelu tarjoaa siten lähtökohdat myös väyläadpositioiden analysointiin: hänen mukaansa terminatiivit ilmaisevat mm. siirtymää (aito liike: Poika juoksi koulusta kotiin asti), sijaintia (fiktiivinen liike: Rautatie menee Helsingistä Turkuun asti), esiintymistä (oliopaljouden tai aineksen hajanainen sijainti: Omenapuita kasvaa Etelä-Suomesta aina Oulun seudulle asti) sekä tilaa, tapahtumista tai toimintaa (= prosessia: tilanteen esiintyminen koko väylän varrella: Sateita esiintyy etelärannikolta Keski-Suomeen asti). Analyysissa ilmenee, että jako sopii myös väyläadpositioiden prepositio- ja postpositioversioiden merkityserojen analysointiin: sijainti- ja siirtymäväylää kuvataan luontevimmin postpositiolla (esim. Juoksin kaupungin halki, Tie ulottuu metsän läpi), esiintymis- ja prosessiväylän ilmaisemiseen taas sopii prepositio (esim. Suppilovahveroita kasvoi siellä täällä läpi metsän ~ ?metsän läpi; Lumipeite oli paksu halki Keski-Suomen ~ ? Keski-Suomen halki). Kuitenkin prepositio on luontevin myös silloin, kun lause implikoi siirtymää mutta verbi ilmaisee muuta seikkaa (Junassa luin kirjaa läpi Keski-Suomen ~ ? Keski-Suomen läpi). Ero heijastaa postposition kiinteämpää suhdetta verbiin ja vastaavasti preposition kehysmäisyyttä sekä itsenäisyyttä lauseytimestä. Tämä itsenäisyys ja kehysmäisyys taas on ominaisuus, joka tekee prepositioista usein postpositioita luontevampia myös temporaalisen merkityksen ilmaisijoita. --- On meaning differences between prepositional and postpositional uses of Finnish path adpositions Though Finnish is a predominantly postpositional language, it also has a significant number of prepositions and many ambivalent adpositions that can be used in both functions (for an overview, see Grünthal 2003). Most of these ambivalent adpositions indicate a path and have meanings such as ‘via’, ‘through’, ‘along’, ‘across’, and ‘over’. Though the received view proposes that the main difference between these variants is stylistic rather than semantic, it has been pointed out that there are also a number of crucial meaning differences between the prepositional and postpositional variants of a few adpositions, most remarkably kautta ‘via’ and pitkin ‘along’. The most prominent and systematic meaning contrast seems to go between the meanings of actual motion (typical for postpositions) vs. the directional representation of static existence or occurrence of entities along the path (typical for prepositions). The latter type is illustrated by Talmy’s (2000: 71) English example There is a house every now and then through the valley, which utilizes a sequential perspectival mode involving a moving proximal perspective point and a local scope of attention, thus a directional, subjective scanning over the static configuration. Such expressions clearly belong to the well-known category of fictive motion (a canonical example of which is The highway goes from Helsinki to Turku) since there is no mover traversing the path and the construal of the path is based on a subjective operation by the conceptualizer. In this article the writer argues that all ambivalent path adpositions are capable of indicating semantic contrasts of the kind outlined above. Their postpositional use is better compatible with expressions of actual motion, while their prepositional use allows a much freer subjective construal of the path. Consider examples (1) and (2), where the adposition läpi ‘through’ indicates actual motion in 1 (postposition; preposition is also possible) and fictive motion (of the type reminiscent of Talmy’s example with the houses) in 2 (only preposition is possible). (1) Juoks+i+mme metsä+n läpi. ~ läpi metsä+n. run+PST+1PL forest+GEN through ~ through forest+GEN ‘We ran through the forest.’ (2) Sien+i+ä kasv+o+i mon+in paiko+in läpi metsä+n. mushroom+PL+PAR grow+PST+3SG many+PL.INS place+PL.INS through forest+GEN ‘There were mushrooms growing in many places throughout the forest’. What such pairs of examples demonstrate is that the meaning of the postposition is more strictly confined to actual motion, whereas prepositions are more flexible in meaning – like postpositions, they can indicate actual motion (as example 1 shows), but to indicate meanings such as that in example 2, a preposition must be used. From a grammatical point of view, the path expression in example 2 has greater autonomy from the clause nucleus than canonical path expressions in examples like 1. In fictive motion the directionality is external to the event designated by the verb and its core arguments (which are not in motion along the path), and thus the path expression takes on the function of a setting adverbial: it indicates a directional frame and a moving perspective to the situation, without being dependent on the activity that takes place between the participants situated within the setting. What distinguishes a path setting from a static setting is the conceptual operation involving the serialization and scanning through the static configuration in a part-by-part manner. A typology of paths well suited for the analysis of path adpositions is introduced by Alhoniemi (1978) in his study of Finnish terminative expressions (‘all the way to/from X’, ‘as far as X’, ‘even in X’ ). These indicate a spatial or other kind of boundary for an event or entity. Alhoniemi (1978) distinguishes four types of terminative paths: paths of transition (paths of actual motion), paths of location (paths of canonical fictive motion, as in The highway goes all the way from Helsinki to Turku), paths of occurrence (paths occupied by an unbounded quantity of entities or a substance, such as in Talmy’s example with the houses in the valley), and paths of states, events, or activities, i.e. processes in Cognitive Linguistic terminology (paths along which a process takes place, as in It rains across the whole country). It turns out that, from the viewpoint of Finnish path adpositions, a crucial distinction runs between A) paths of transition and location on the one hand and B) paths of occurrence and process on the other hand. In general, it is more natural to use a postpositon to indicate a type A path and a preposition to indicate a type B path. Thus, in Talmy’s terminology, prepositions favour the proximal perspective point, whereas postpositions select the alternate conceptualization strategy called the synoptic perspectival mode, which keeps the whole configuration “in sight” throughout the event. This difference also explains why prepositions (more easily than postpositions) evoke the meaning of unboundedness for their landmark and sometimes even for aspect – the proximal perspective conceals the overall boundaries of the landmark and the process from the window of attention it indicates. In contrast, postpositions typically include the reaching of the other side of the landmark within their scope of meaning. In general, the phenomena discussed in this article show that the relationship between a path expression and the clause nucleus varies to a considerable degree, and features numerous intermediate stages. At the one end of the continuum is a canonical path, which is traversed by one single trajector that proceeds from one end of the path to the other, while at the other end we have expressions where the path is the starting point for the predication, the selected direction is purely subjective, the entity or entities occupying the path remain static and the verb indicates no motion but rather another kind of a process.